2019
DOI: 10.1213/ane.0000000000003377
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Periarticular Ketorolac in Adult Patients Undergoing Total Hip or Total Knee Replacement Surgery

Abstract: Our study demonstrates that with periarticular infiltration, S (-) ketorolac was observed to have increased clearance rate and highly variable volume of distribution and lower peak plasma concentration compared to R (+) ketorolac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Studies by Yang HL et al suggested that injection of ketorolac tromethamine before tracheal intubation can reduce the incidence of sore throat caused by endotracheal intubation from 71.6 to 21.1% [23]. Compared with other NSAIDs, ketorolac tromethamine has a weaker anti-inflammatory effect and stronger analgesic effect and has been widely used in the clinic [10,24]. In this study, ketorolac tromethamine significantly reduced the number of patients with VAS scores greater than 3.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Studies by Yang HL et al suggested that injection of ketorolac tromethamine before tracheal intubation can reduce the incidence of sore throat caused by endotracheal intubation from 71.6 to 21.1% [23]. Compared with other NSAIDs, ketorolac tromethamine has a weaker anti-inflammatory effect and stronger analgesic effect and has been widely used in the clinic [10,24]. In this study, ketorolac tromethamine significantly reduced the number of patients with VAS scores greater than 3.…”
Section: Discussionmentioning
confidence: 48%
“…We describe the relevant effects objectively because there is no relevant report about ketorolac tromethamine injection or other nonsteroidal drugs inhibiting sufentanil-induced cough. Second, the pretreatment dose of ketorolac tromethamine that was used (0.5 mg/ kg) may not be the most appropriate dose for ketorolac tromethamine to inhibit the sufentanil-induced cough response, but it was given according to the early postoperative analgesic dose recommended in the drug instructions [10]. Third, our study was a single center study with a small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nteroidal anti-inflammatory drugs (NSAIDs) play important roles in the multimodal analgesic protocol (Moizo et al, 2004;Ismail et al, 2020;Özden & Kiliç, 2020;Yuwa-Amornpitak et al, 2020). Ketorolac tromethamine, otherwise known as ketorolac, is a NSAID and a pyrrolizine carboxylic acid derivative (Gurunathan et al, 2018). It is currently one of the most effective non-steroidal anti-inflammatory drugs and widely used in adult postoperative analgesia (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%